POTENSI PRODUKSI DAN KEBUTUHAN BENIH UNTUK PENGEMBANGAN PERIKANAN TANGKAP DI EMBUNG NUSA TENGGARA TIMUR - Warsa, Andri; Krismono, Krismono (Research Center for Limnology, 2018)
Embung or retention basin is one of the surface water sources in the form of artificial lake obtained from harvesting the rain and surface water. East Nusa Tenggara (NTT) Province has built 963 retention basins and three dams which are used mainly for irrigation, plantation, and livestock, while for fisheries it has not been developed optimally. The development of capture fisheries through the stocking of fish seeds is one of the efforts to optimize the utilization and management of water bodies. The failure of fish stockings in several water bodies in NTT is thought to be caused by lack of scientific studies before the stockings. Therefore, the purpose of this research was to determine the potential of fisheries production and the optimal number of seeds for the development of capture fisheries in the retention basins of NTT. The research was conducted in September 2016. Water samples were taken at a depth of 0.5 m from the surface using the Kemmerer water sampler. Secondary data which included fish growth parameters were obtained from literature, while seed production and morphological characteristics of water bodies were obtained from relevant institutions. The results showed that Embung Tulamalae and Oelpuah were eutrophic, while Embung Haekrit and Haliwen were oligotrophic. The average potential of fisheries production based on MEIcond ranged 41.3−68.7 kg/ha/year with an average of 52.8 kg/ha/year, while based on chlorophyll a content ranged 29.8‒55.8 kg/ha/year with an average of 43.6 kg/ha/year. Estimation of seed requirements for restocking in the context of developing capture fisheries ranged from 1,000 to 48,600 individuals/year. Based on the water quality and economic values obtained, embung at the research locations are feasible for fish stocking in the capture fisheries development.